Damaged Insula Network Contributes to Depression in Parkinson’s Disease - Huang, Peiyu; Guan, Xiaojun; Guo, Tao; Zeng, Qiaoling; Xuan, Min; Gu, Quanquan; Xu, Xiaojun; Zhou, Cheng; Wu, Jingjing; Zhang, Minming (Frontiers in Psychiatry, 2020)
Background: Depression is a common occurrence in patients with Parkinson’s disease (PD). Our previous studies suggest that depressed PD patients had altered insula structures. Though, it is still unknown whether the altered structures could cause disruption of insula functional networks and further contributes to depression in PD. Methods: In the present study, seventeen depressed PD patients, 17 non-depressed PD patients and 17 normal controls were enrolled. All subjects went through neurological and psychiatric clinical assessments. Resting-state functional magnetic resonance imaging and seed-based insula functional analyses were performed to examine the insula functional connectivity alterations in PD patients. Results: We found that compared with normal controls, PD patients exhibited significantly decreased insula functional connectivity widely across the whole brain. Compared with non-depressed PD patients, depressed patients showed further decreased functional connectivity in middle frontal gyrus and inferior parietal lobe. Besides, connectivity between left anterior insula and middle frontal gyrus was positively correlated with the cognitive scale score. Conclusion: These results suggest that insula networks had been severely damaged in PD patients, and that the disrupted connection between salience network and executive control network might contribute to depression in PD.